2020
DOI: 10.1111/1471-3802.12495
|View full text |Cite
|
Sign up to set email alerts
|

The importance of self‐regulation: a mediator of early socio‐emotional difficulties on later socio‐emotional and relational outcomes

Abstract: Research suggests that a childhood diagnosis of Autism Spectrum Disorder (ASD) or Attention Deficit Hyperactivity Disorder (ADHD) is associated with poorer teacher–child relationship quality and higher rates of externalising behaviours. It is proposed that the socio‐emotional problems experienced by those children with ASD and/or ADHD lead to poor teacher–child relationship quality and an increase in externalising behaviours. It is also proposed that self‐regulation skills and language ability may mediate thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
2
0
2
Order By: Relevance
“…Although relationship self‐regulation is generally thought of as an individual process, their research documented an interpersonal dimension to also exist that paves the way for positive relationships among relationship self‐regulation strategies, effort, and relationship satisfaction. Nucifora and Walker's (2021) study supported the conclusion that self‐regulation is a protective factor for people who've been diagnosed with disorders associated with socioemotional problems. Their results also reported that a focus on self‐regulation skills in education programs has the potential to improve socio‐relational outcomes for all children with socioemotional difficulties.…”
Section: Introductionmentioning
confidence: 80%
“…Although relationship self‐regulation is generally thought of as an individual process, their research documented an interpersonal dimension to also exist that paves the way for positive relationships among relationship self‐regulation strategies, effort, and relationship satisfaction. Nucifora and Walker's (2021) study supported the conclusion that self‐regulation is a protective factor for people who've been diagnosed with disorders associated with socioemotional problems. Their results also reported that a focus on self‐regulation skills in education programs has the potential to improve socio‐relational outcomes for all children with socioemotional difficulties.…”
Section: Introductionmentioning
confidence: 80%
“…While there is literature on the negative impacts of ADHD on children's HRQoL (Lloyd et al., 2011 ; Nucifora & Walker, 2021 ), the association between SES with HRQoL for children with ADHD has largely been unexplored. We found only two studies that investigated this topic, both of which found an impact of SES on HRQoL of children with ADHD: Owens ( 2020 ) reported a negative association between SES and perceived self‐competence and school behaviours among medicated children with and van der Kolk et al.…”
Section: Discussionmentioning
confidence: 99%
“…Elevernas beteende, som stundtals uppfattas vara utagerande, tenderar att påverka lärares känslor, och på lång sikt även deras interaktion, med dessa elever (Nucifora & Walker, 2021). Det utagerande beteendet verkar också vara det största hindret för goda lärar-elev-relationer (Zendarski et al, 2020) och det som lärare upplever som mest utmanande i relationen till dessa elever .…”
Section: Relationen Mellan Lärare Och Elever Med Adhdunclassified
“…De tre subkategorierna ska förstås som verktyg som kan fungera som stöd vid identifikation och analys av viktiga, men sällan noterade, kvaliteter i lärares interaktioner med elever . När det gäller arbetet med att undervisa elever med ADHD har det visat sig att det ofta finns tillkortakommanden hos lärare avseende förmågan att bygga relationer (Nucifora & Walker, 2021), samtidigt som elever ofta upplever att deras relationer till lärare brister . Utifrån teoretiska antaganden om sociala band (Scheff, , 1990, och RCM som analysmodell för hur relationer kan förstås och utvecklas i klassrummet har denna avhandlings studier utformats, i förlängningen med intentionen att utveckla lärares klassrumspraktik och möten med elever med ADHD.…”
Section: Relationskompetensmodellenunclassified